Genetic polymorphism of CYP2D6*10 gene among Filipinos - Baclig, Michael O.; Predicala, Rey Z.; Mapua, Cynthia A.; Daroy, Maria Luisa G.; Tiamson, Ma. Elena B.; Palabrica, Maria Luisa D.; Atillo, Roy P.; Torres, Ronald Allan R.; Tobias, Sheryl S.; Javier, Francis O.; Natiidad, Filipinas F. (2011)
Cytochrome P450 (CYP2D6) is one of the major drug metabolizing enzymes involved in the biotransformation of many clinically important medications including opioid analgesics. CYP2D6 enzyme activity varies considerably within a population. Particularly, CYP2D6*10 allele is more common among Orientals than among Caucasians. A recent study among Chinese individuals showed that the allele frequency of CYP2D6*10 (C188T) was about 37-70%. Phenotypic expressions include individuals with ultrarapid, extensive intermediate, and poor metabolizer status. It has been shown that the various phenotypes have profound effects on the efficacy of drugs as well as its adverse reactions. In this study we determined the allele and genotype frequencies of CYP2D6*10 among Filipinos using PCR-RFLP and sequence analysis. Blood samples were obtained from healthy study participants and patients with chronic pain, with diagnosed cancer pathology stages 1 to 4. The calculated allele frequencies in Hardy Weinberg equilibrium were 0.49 and 0.51 for the CYP2D6*10 dominant and recessive alleles, respectively. Out of the seventy seven samples, 18 (23%) were identified as homozygous for the wild type, 40 (52%) were identified as heterozygous, and 19 (25%) were identified as homozygous for the mutant allele. Our results showed that majority of the Filipinos were heterozygous for the intermediate allele (52%). PCR-RFLP and sequence analysis provides a useful tool for CYP2D6*10 genotyping. The allele frequency of CYP2D6*10 was comparable with other Asian populations. Individuals heterozygous for the intermediate allele were found to be predominant genotype among Filipinos.
Keywords: Genetic polymorphisms